Evaluation of C-ErbB-2 Overexpression and Her-2/neu Gene Copy Number Heterogeneity in Barrett’s Adenocarcinoma - Axel Walch; Karin Bink; Peter Gais; Stefan Stangl; Peter Hutzler; Michaela Aubele; James Mueller; Heinz Höfler; Martin Werner (Analytical Cellular Pathology)
Amplifiction of the Her-2/neu gene is accompanied by overexpression of its cell surface receptor product, c‐erbB‐2 protein. To investigate the degree of intratumoural heterogeneity we applied immunohistochemistry in primary Barrett’s adenocarcinoma (BCA) (n = 6) and dysplasia adjacent to the carcinoma (n = 4). In addition, fluorescence in situ hybridisation (FISH) was performed in primary BCA (n=5) and dysplastic areas (n=4). For an objective evaluation digital image analysis and laser scanning microscopy were used. Five of six BCA showed a marked intratumoural heterogeneous staining pattern ranging from areas in which the tumour cells were negative or faintly positive to tumour areas with a strong staining of the entire membrane. Among the two dysplastic areas also a heterogenous staining pattern was observed. FISH analysis revealed marked heterogeneity of intratumoural gene copy number changes in all BCA showing populations with different fractions of cells with polysomy, low level amplification and high level amplification. One dysplasia showed a minor population with Her‐2/neu signal clusters. In conclusion, we observed marked intratumoural heterogeneity of c‐erbB‐2 protein overexpression and Her‐2/neu gene copy number in the majority of the primary BCA analyzed. Digital image analysis and laser scanning microscopy were helpful in quantifying the variations in protein expression and DNA copy number in individual tumour cells. The observed heterogeneity could hamper the exact diagnostic determination of the c‐erbB‐2 status in small biopsies and possibly influence the effectiveness of a potential c‐erbB‐2 targeting therapy.